Prácticas de crianza en madres de estratos socioeconómico medio y bajo de Lima - Majluf, Alegría (1989)
A comparative study on child-rearing practices reported by 6and 7 yearold children's mothers, evidenced significant differences between middle - and low - SES mothers. The fonner being more democratic; the latter, more authoritarian. With Block' s Child-Rearing Practices Report differences emerged with regard to authoritarian control, control by anxiety, and supervision (Authoritarian style ), and also with regard to independence enhancement, expressiveness, and rational orientation (Democratic). Other differences were observed conceming maternal role enjoyment, toilet training, and sexual repression. No ~fferences were found on achievement orientation and expectations".